Intussusception of the jejuno-jejunal anastomosis in a patient with Roux-en-Y gastric bypass - Palomares-Leal, Alain; Morales-Cardona, Antonio; Cortinas-González, Julio Cesar; Sifuentes-Gallardo, Rogelio Alejandro; Campos-Cruz, Carla Paulina; Cruz-Hernández, Samantha Jazmín De La; Silva-Martínez, Juan Pedro (International Surgery Journal, 2023)
Intussusception is a rare complication in postoperative patients undergoing Roux-en-Y gastric bypass (RYGB), with an incidence of 0.64%. The clinical presentation usually involves severe abdominal pain, accompanied by nausea and vomiting. The diagnostic approach using imaging studies involves computed tomography, revealing the radiological "target" sign. The treatment is surgical, with the lowest recurrence rate (12.5%) observed in the resection and anastomosis of the intussuscepted segment. The objective is to present the case of intussusception at the jejuno-jejunal anastomosis in a postoperative RYGB patient, along with its therapeutic approach, in a hospital in northern Mexico.